Ethical climate and missed nursing care in cancer care units - Vryonides, Stavros; Papastavrou, Evridiki; Charalambous, Andreas; Andreou, Panayiota; Eleftheriou, Christos; Merkouris, Anastasios (My University, 2018)
Previous research has linked missed nursing care to nurses' work environment. Ethical climate is a part of work environment, but the relationship of missed care to different types of ethical climate is unknown.
Keywords: Cancer care units; Care rationing; Hematology; Missed nursing care; Oncology; Types of ethical climate